Neuroprotective Effect of Ligustilide through Induction of α-Secretase Processing of Both APP and Klotho in a Mouse Model of Alzheimer’s Disease - Kuang, Xi; Zhou, Hong-Jing; Thorne, Amy H.; Chen, Xi-Nan; Li, Lin-Jiao; Du, Jun-Rong (Frontiers in Aging Neuroscience, 2017)
Emerging evidence suggests that alpha-processing single transmembrane proteins, amyloid precursor protein (APP) and anti-aging protein Klotho, are likely to be involved in the progression of Alzheimer’s disease (AD). The natural phthalide Ligustilide (LIG) has been demonstrated to protect against aging- and amyloid-β (Aβ)-induced brain dysfunction in animal models. The present study is to investigate the effects of LIG on cognitive deficits and metabolism of both APP and Klotho and its underlying mechanism in AD double-transgenic (APP/PS1) mice and cultured human cells. Our results show that treatment with LIG significantly ameliorated memory impairment and Aβ levels and plaques burden. Specifically, LIG might act as a potent enhancer of α-secretase, disintegrin and metalloprotease 10 (ADAM10), leading to upregulation of alpha-processing of both APP and Klotho and subsequent increases in the levels of both soluble APP fragment (sAPPα) and soluble Klotho (sKL) with inhibition of IGF-1/Akt/mTOR signaling in AD mice and cultured cells. Moreover, the specific ADAM10 inhibitor (G1254023X) effectively reversed LIG-induced alpha-processing of both APP and Klotho in vitro, while Klotho gene knockdown by small interfering RNA (siRNA) significantly blunted LIG-mediated inhibition of IGF-1/Akt/mTOR signaling in vitro. Taken together with reported neuroprotective effects of both sAPPα and sKL as well as autophagy induction by Akt/mTOR pathway inhibition, our findings suggest that neuroprotection of LIG against AD is associated with induction alpha-processing of APP and Klotho and potential Aβ clearance. Whether LIG might induce Aβ autophagic clearance and the underlying mechanisms need to be further studied.